Evaluation of the QMS® Teicoplanin Immunoassay (ThermoFisher Scientific) on Cobas® 8000 System (Roche Diagnostics) and Comparison to Fluorescence Polarization Immunoassay for the Determination of Teicoplanin Concentrations in Human Plasma. Issue 2 (1st February 2013) - Dailly, Eric; Fraissinet, François; Deslandes, Guillaume; Bouquié, Régis; Jolliet, Pascale
Abstract : Background: The performances of the QMS ® Teicoplanin immunoassay recently developed on Cobas ® 6000/8000 systems were evaluated and compared to a fluorescence polarization immunoassay (FPIA) [Teicoplanin Innofluor ® Assay (Thermo Fisher Scientific, Indianapolis, IN)] on FLX analyzer (Abbott Laboratories, Abbott Park, IL)]. Methods: The validation was performed according to the Cofrac (French Accreditation Committee) document SH GTA 04. For the comparison, 48 plasma samples were analyzed by FPIA and QMS assays. Results: The QMS assay is accurate (intra assay and inter assay inaccuracy ≤ 2.4%) and precise (intra assay and inter assay imprecision ≤ 10.2%). A linear relationship [QMS = 1.0319 × FPIA – 2.8518, r 2 = 0.9246 ( P < 0.001)] between FPIA and QMS was found. In the Bland—Altman plots, no systematic bias was found even if QMS results trends to be lower (mean of the ratio QMS concentration/FPIA concentration = 0.91). Conclusion: These results between QMS and FPIA are consistent, which indicates that QMS ® Teicoplanin immunoassay on Cobas ® 8000 System is an alternative to FPIA. J. Clin. Lab. Anal. 27:96–98, 2013. © 2012 Wiley Periodicals, Inc.